Effects of different corticotomy approaches on anterior retraction with clear aligners: a finite element study - Hongyu Hou; Fang Yang; Hong He; Fang Hua; Zhengguo Cao; Hui Xiong (BMC Oral Health)
Abstract Background Corticotomy has been shown to influence the biomechanical behavior of dentoalveolar structures during anterior retraction. However, most research on corticotomy in orthodontics focused on fixed appliance models. This study aimed to investigate the biomechanical effects of different corticotomy approaches that facilitate anterior retraction with clear aligners. Methods Based on research criteria, one volunteer was selected(24 years old, male) and cone beam computed tomography (CBCT) data were obtained. Finite element models were constructed using reverse engineering, including maxillary dentition without first premolars, maxilla, periodontal ligaments (PDLs), attachments, and aligners. Four models with varying corticotomy approaches were developed: Model 1 (no corticotomy), Model 2 (corticotomy with bilateral horizontal and vertical incisions), Model 3 (corticotomy with unilateral buccal horizontal and vertical incisions), and Model 4 (corticotomy with unilateral buccal vertical incisions). Stress distribution in the PDLs and alveolar bone, as well as initial anterior tooth displacement, were computerized and evaluated using three-dimensional finite element analysis. Results Stress distribution in the PDLs was similar across all models, with tensile stress concentrated at labial region of the coronal third of the root and lingual apical region and compressive stress at lingual region of the coronal third of the root and labial apical region. Differences were observed in stress distribution within the alveolar bone across all models. After corticotomy, stress concentration in the alveolar bone decreased in the incision regions but increased around the extraction space. Anterior teeth demonstrated lingual and distal inclination across all models. Models with horizontal and vertical incisions (Models 2 and 3) exhibited more significant crown displacement and more pronounced inclination compared to Model 1. The effects were more prominent in bilateral incisions compared to unilateral ones. Conclusions Corticotomy affected the mechanical response of alveolar bone during anterior retraction, promoting bone remodeling and tooth movement. Incisions near the apical region or aligned with the direction of tooth movement may better facilitate anterior retraction. During anterior retraction with clear aligners, anterior teeth exhibited tipping movement, and corticotomy modified this movement pattern. Horizontal and vertical incisions may exacerbate the inclination of anterior teeth. The changes in tooth movement patterns after corticotomy should be carefully considered in orthodontic treatment planning.